Senses of place masyarakat Kampung Lawas Maspati Surabaya: Studi eksplorasi terhadap faktor fisik, sosial dan budaya - Diyan Lesmana; Antariksa; Lisa Dwi Wulandari; Herry Santosa (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The Lawas Maspati village in the Surabaya urban area has relics such as historical areas, ancient buildings with colonial architectural styles, and community cultural traditions such as the mutual cooperation attribute, cangkrukan (gathering), and local wisdom (culinary, craft SME). The efforts towards maintaining the heritage buildings and adapting to cultural dynamics as well as the local wisdom make Lawas Maspati Village a life diorama which allows a person to have a sense of place towards the village. This study was conducted to explore the sense of place in the Lawas Maspati Village community through physical, social, and cultural factors through the use of a qualitative descriptive method with a phenomenological approach. Data were collected through in-depth interviews and field documentation from respondents selected through a purposive sampling method using individuals that have lived for more than 20 years and aged over 40 years old. The results showed the sense of place in Lawas Maspati Village community was formed by physical, social, and cultural factors including the ancient colonial-style buildings, historical areas, historical memories in the struggle period through cultural heritage areas, mutual cooperation, mutual respect, cangkrukan tradition, friendly characteristics of Arek Suroboyo such as tolerance, openness, busyness but friendliness without hurt feelings, traditional culinary, and religious traditions.